Multilayer DNA Origami Packed on Hexagonal and Hybrid Lattices - Ke, Yonggang (2012)
“Scaffolded DNA origami” has been proven to be a powerful and efficient approach to construct two-dimensional or three-dimensional objects with great complexity. Multilayer DNA origami has been demonstrated with helices packing along either honeycomb-lattice geometry or square-lattice geometry. Here we report successful folding of multilayer DNA origami with helices arranged on a close-packed hexagonal lattice. This arrangement yields a higher density of helical packing and therefore higher resolution of spatial addressing than has been shown previously. We also demonstrate hybrid multilayer DNA origami with honeycomb-lattice, square-lattice, and hexagonal lattice packing of helices all in one design. The availability of hexagonal close packing of helices extends our ability to build complex structures using DNA nanotechnology.